The Reality of Implementing of E-learning in Graduate Studies Programs from the Point of View of Postgraduate Students at King Saud University - Al-Mansour, Haila Abdulaziz (Journal of Educational and Psychological Sciences, 2019)
This study aims to recognize the reality of e-learning application in graduate study programs in the point of view of the girl students of the graduate study in King Saud University. The study has used the descriptive approach through the application of questionnaire that involved three points: using some e-learning tools which depend on the internet, the girl student's satisfaction for the application of the e-learning and its obstacles in the graduate study programs. And it was applied to a random sample from the graduate study girl students of the faculty of education that reached (220) girl students, 182 students responded for it. And after collecting the data and analyzing them by using repetition, percentages, arithmetic means and the study has reached many important results such as: The use of some e-learning means that depend on the internet. The study focused on satisfaction of the girl students for the application of e-learning, and the application obstacles. As well as ,it was applied on a random sample of the graduate study girl students in the faculty of education which had 220 girl students, there were 182 responded students and analyzing the data after collecting them using a number of statistical ways and the study has reached some important results: The e-learning means which depend on the internet that was applied in the graduate study programs of King Saud University in the sample's point of view and it came in the following order: The web net is the most used means of the electronic education and then the electronic emails, after that the scientific electronic forums. Finally, the blogs and the social networks such as: face book, twitter and YouTube. The study has found that the satisfaction of the sample persons for the application of the e-learning divided into two categories: (satisfied and unsatisfied).The study results have confirmed that the obstacles ranged from medium, small and zero. The weakness in the English Language was a medium obstacle, while the cost of the internet connection was high, the lack of the teachers who encourage to the use of the electronic learning, there is no interaction of the teachers during the use of electronic learning, and the lack of the teachers who are able to use the e-learning are small obstacles for the persons of the sample. This study has provided a number of suggested procedures recommendations which aim to the improvement of the e-learning in the graduate study programs, they included (suggested programs to develop the girl students in the field of electronic learning, suggested programs to develop the teachers in the field of electronic learning, Suggested programs to develop the e-learning planning in the university).
Keywords: E-Learning; E-Learning Tools; Obstacles; Application; Graduate Study Programs